Halal Administration and Branding in Muslim Minority Countries: A Case of Uganda - Aina-Obe Shamsuddin Bolatito; Shifa Wahab (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
As the global Muslim market grows, halal branding is seen to be an emotional appeal to many practicing Muslims and hence perceived to be an effective marketing strategy for many food-producing firms. In Uganda, the concept of Islamic branding has not yet received full attention. Therefore, it is worth investigating the factors that affect Halal administration and branding in Muslim-minority countries. This study provides an in-depth examination of the administration and branding of halal goods by exploring the dynamic evolving landscape arena of Halal administration and branding with a particular emphasis on the scenario in Uganda. The research examines the several facets of halal certification, including its benefits within Islamic dietary regulations and the obstacles encountered in guaranteeing adherence. It delves into the significance of branding in promoting halal goods and establishing a competitive edge for firms operating in countries with Muslim minority populations. The study utilizes reputable print materials, academic journals, and website information to comprehensively examine the subject matter. The research further seeks to enhance the overall comprehension of Halal procedures in Muslim minority situations and provide an organized approach for similar nations grappling with the intricacies of Halal certification and branding. Challenges such as standardization, consumer awareness, and supply chain integrity are critically assessed thereby proposing strategic approaches for overcoming these challenges, emphasizing the need for collaboration between governmental, religious, and commercial entities